Systematic review on parental divorce and its psychological impact on children (Jóvenes en la Ciencia, 2026)
Parental divorce is a phenomenon of increasing prevalence globally and in Mexico, with significant implications for child development. This systematic review analyzes existing scientific literature on the psychological impact of divorce on children aged 3 to 12 years, aiming to identify how this phenomenon affects their development in the short and long term, and to determine the mediating role of parental conflict.Through a review of 15 articles from specialized databases, it was found that divorce per se is not the main risk factor for the development of child psychopathology. The evidence consistently indicates that post-divorce parental conflict emerges as the most influential predictor of psychological difficulties, including anxiety, depression, and disruptive behaviors. Factors such as the triangulation of the child into parental conflicts and the quality of the co-parenting relationship significantly moderate the impact.It is concluded that the consequences of parental divorce are not uniform but critically depend on the relational environment after the separation. These findings highlight the need to develop specialized psychological interventions that promote effective co-parenting and constructive conflict management for both parents and children, in order to mitigate long-term negative consequences.